Early biochemical outcomes following neoadjuvant/adjuvant relugolix with stereotactic body radiation therapy for intermediate to high risk prostate cancer - Gallagher, Lindsey; Xiao, Jerry; Hsueh, Jessica; Shah, Sarthak; Danner, Malika; Zwart, Alan; Ayoob, Marilyn; Yung, Thomas; Simpson, Tiffany; Fallick, Mark; Kumar, Deepak; Leger, Paul; et al. (Frontiers in Oncology, 2023)
Introduction Injectable GnRH receptor agonists have been shown to improve cancer control when combined with radiotherapy. Prostate SBRT offers an abbreviated treatment course with comparable efficacy to conventionally fractionated radiotherapy. Relugolix is a new oral GnRH receptor antagonist which achieves rapid, sustained testosterone suppression. This prospective study sought to evaluate early testosterone suppression and PSA response following relugolix and SBRT for intermediate to high prostate cancer. Methods Relugolix was initiated at least 2 months prior to SBRT. Interventions to improve adherence were not utilized. PSA and total testosterone levels were obtained prior to and 1-4 months post SBRT. Profound castration was defined as serum testosterone ≤ 20 ng/dL. Early PSA nadir was defined as the lowest PSA value within 4 months of completion of SBRT. Per prior trials, we examined the percentage of patients who achieved PSA level of ≤ 0.5 ng/mL and ≤ 0.2 ng/mL during the first 4 months post SBRT. Results Between July 2021 and January 2023, 52 men were treated at Georgetown with relugolix (4-6 months) and SBRT (36.25-40 Gy in 5 fractions) per an institutional protocol (IRB 12-1775). Median age was 71 years. 26.9% of patients were African American and 28.8% were obese (BMI ≥30 kg/m2). The median pretreatment PSA was 9.1 ng/ml. 67% of patients were ≥ Grade Group 3. 44 patients were intermediate- and 8 were high-risk. Patients initiated relugolix at a median of 3.6 months prior to SBRT with a median duration of 6.2 total months. 92.3% of patients achieved profound castration during relugolix treatment. Poor drug adherence was observed in 2 patients. A third patient chose to discontinue relugolix due to side effects. By post-SBRT month 4, 87.2% and 74.4% of patients achieved PSA levels ≤ 0.5 ng/ml and ≤ 0.2 ng/ml, respectively. Discussion Relugolix combined with SBRT allows for high rates of profound castration with low early PSA nadirs. We observed a 96% testosterone suppresion rate without the utilization of scheduled cues/reminders. This finding supports the notion that patients with localized prostate cancer can consistently and successfully follow an oral ADT protocol without daily reminders. Given relugolix’s potential benefits over injectable GnRH receptor agonists, its usage may be preferred in specific patient populations (fear of needles, prior cardiovascular events). Future studies should focus on boundaries to adherence in specific underserved populations.